PENGARUH KUALITAS SISTEM DAN INFORMASI PADA SISTEM INFORMASI PEMBELAJARAN ONLINE TERHADAP MINAT PENGGUNA DAN PENGGUNAAN SISTEM (STUDI KASUS: SIMPONI AMIK MDP, STMIK GI MDP DAN STIE MDP) - Mulyati Mulyati; Anggoro Aryo P; Dorie Pandora K (Jurnal TAM (Technology Acceptance Model), 2017)
System Quality and Information Quality are twodimensions which are interrelated in the Information Technologies’s application usage. Those both qualities determinethe output wich is created from electronic learning system as one of the utilization of IT’s ineducation.Because of that, the development and inovation in electronic learning systems are absolutely done by the education institute.Nowadays, universities are also competing to increase the benefit of IT’s in learning-teaching system based on IT.Some of universities held and organize electronic learning as an additionalactivitiesin its lesson as they presented in class regularly.AMIK MDP,STMIK GI MDP and STIE MDP are currently applied these system in their academic lesson activities.These  research aimed to determine the influence ofSystem Quality and Information Quality to the User Interest and System Usage of online learning system in SIMPONI AMIK MDP, STMIK GI MDP, and STIE MDP.Authors use questionaire method in these data collection, the Structurel Equation Modelling(SEM) method and SmartPLS V2.0M3 assistance are done in processing and data analize.These research is expecting that the authors can give they contribution to the management in what shall be taken for the next step decision in internet utillization by students in AMIK MDP,STMIK GI MDP, and STIE MDP to maximize the academic process.